The Use of Etoposide, Ara-Cytarabine, and Melphalan (EAM) Conditioning Chemotherapy in Autologous Stem Cell Transplantation (ASCT) for a Patient with Relapsed Hodgkin’s Lymphoma - Pangarsa, Eko A.; Naibaho, Ridho M.; Yunarvika, Vina; Setiawan, Budi; Santosa, Damai; Suharti, Catharina (Case Reports in Hematology, 2021)
Up to 20–40% of patients with Hodgkin’s lymphoma will eventually relapse after treatment, among which early relapse confers a poor outcome. With salvage chemotherapy followed by autologous stem cell transplantation (ASCT), the long-term remission rate is 30%. We report our experience of using a modified-BEAM conditioning regimen without BCNU consisting of etoposide, cytarabine, and melphalan (EAM) in a patient with relapsed Hodgkin’s lymphoma. Before transplantation, the patient achieved second complete remission (CR2) using brentuximab vedotin and ESHAP (BR-ESHAP) chemotherapy. The ASCT went well without significant complications. This case demonstrated the considerable efficacy of EAM protocol as a conditioning regimen in terms of sufficient ablative capabilities, and the patient showed a successful hematopoietic engraftment. Although durability of the disease-free survival needs further observation, it had nearly 18 months of complete remission and the patient was in good performance status at the time of writing this manuscript.